From Competition to Configuration - Trinanda, Ghea Anissah (PCD Journal, 2024)
This article examines the transformation of two types of knowledge—government/official knowledge, which represents "scientific" and “expertise”; and local knowledge, represented by the "Jalin Merapi" community, considered as “non-scientific” and layman's understanding. Both types of knowledge are linked by a common "boundary object" (Gieryn, 1983) of Mount Merapi, but they are often in a competition to influence public discourse. The main argument of this article is that integrating government/scientific and local/non-scientific knowledge can result in more effective disaster mitigation strategies. However, in Indonesia, there is a significant gap between these two types of knowledge systems, and competition often overshadows collaboration. Using a qualitative case study approach, the research highlights a shift in knowledge dynamics, from competition to collaboration, facilitated by the "Jalin Merapi" community. Despite this progress, the inclusion of local knowledge in policy making in Indonesia remains limited. This finding emphasises the importance of more inclusive policies that combine scientific knowledge with local insights to improve disaster management system in Indonesia.